Some observations on the radiocarbon and cosmogenic isotope dating of petroglyphs, Foz Côa, Portugal - Watchman, Alan
Further remarks on the age of the Foz Côa rock-engravings, Portugal, in the light of studies by absolute-science methods in the March 1997 ANTIQUITY.